Studying the Role of Haptic Feedback on Virtual Embodiment in a Drawing Task - Richard, Grégoire; Pietrzak, Thomas; Argelaguet, Ferran; Lécuyer, Anatole; Casiez, Géry (Frontiers in Virtual Reality, 2021)
The role of haptic feedback on virtual embodiment is investigated in this paper in a context of active and fine manipulation. In particular, we explore which haptic cue, with varying ecological validity, has more influence on virtual embodiment. We conducted a within-subject experiment with 24 participants and compared self-reported embodiment over a humanoid avatar during a coloring task under three conditions: force feedback, vibrotactile feedback, and no haptic feedback. In the experiment, force feedback was more ecological as it matched reality more closely, while vibrotactile feedback was more symbolic. Taken together, our results show significant superiority of force feedback over no haptic feedback regarding embodiment, and significant superiority of force feedback over the other two conditions regarding subjective performance. Those results suggest that a more ecological feedback is better suited to elicit embodiment during fine manipulation tasks.